A flash characterisation method for thin cylindrical multilayered composites based on the combined front and rear faces thermograms. Issue 2 (2nd July 2016) - Duquesne, Loys; Lorrette, Christophe; Pradère, Christophe; Vignoles, Gérard Louis; Batsale, Jean-Christophe
Abstract: The flash method, known as the most used experimental technique to measure the thermal diffusivity of solids, has been adapted to cylindrical highly diffusive and heterogeneous multilayered samples. In order to overcome the heterogeneities issue and give a more accurate estimation of the sample thermal properties, the front face and rear face thermal responses have been simultaneously recorded using an infrared camera. A homogeneous monolithic SiC cylinder has been tested to validate this experimental method which has finally been applied to 2D bi-layered SiCf/SiC cylinders used for nuclear fuel cladding.